(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Documentary Credit passes through many practical phases starting from Opening credit and matching documents and payment of the amount of credit……etc. It is worthy to mention that there are several aspects that are varied and differed from Bank to another one which can offer Competitive Advantage for the bank …This will be shown in this research. For the purpose of achieving the objective of this research within the theoretical aspect, the researcher had seen and briefed several books and researches which are mainly related to the subject of the research. As for the practical aspect, has included Questionnaire which included many questions that are fit and suitable to the hypotheses. Research sample has involved Private Iraqi Banks "North Bank for Finance and Investment" and "The United Bank for Investment". Sixty Questionnaires were distributed for the Bank’ Clients "Research Sample". The most significant conclusions, the research has achieved, to find Correlation with significance between the Rate of Cost and the Documentary Credit in Banks "Research Sample". The most important recommendations is concentrating in Putting the currency quotes fit with the quality of the offered service doesn’t affect against customer satisfaction.